Synthesis and Characterization of Ba0.6Sr0.4Fe12O19/LaMnO3 Composites as Microwave Absorbers - Yohanes Edi Gunanto; Maya Puspitasari Izaak; Henni Sitompul; Wisnu Ari Adi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
The synthesis and characterization of Ba0.6Sr0.4Fe12O19/LaMnO3 composite material has been successfully carried out by mechanical alloying method using high energy milling. Crystal structure and surface morphology were characterized using x-ray diffraction and scanning electron microscopy. While the value of magnetization and the ability to absorb microwaves, vibrating sample magnetization and vector network analyzing were used, respectively. With variations in weight, does not change the crystal structure. The Ba0.6Sr0.4Fe12O19phase has a hexagonal structure and the LaMnO3 phase has an orthorhombic structure. Surface morphology has a heterogeneous size in the range of 200-450 nm with the form of platelets. The composite material Ba0.6Sr0.4Fe12O19/LaMnO3 is a hard-soft magnetic material with a magnetic saturation of Ms ~ 46.83 emu/g, Mr ~ 28.8 emu/g, and a coercive field of Hc ~ 3.88 kOe. The minimum reflection loss value is – 13.0 dB at 11.2 GHz frequency and 1.52 GHz bandwidth.